The terpenoid emission pattern of Quercus coccifera L coincides with the emission pattern found with Quercus ilex L - Hansen, U.; Seufert, G. (PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION, 1997)
Monoterpene and isoprene emission rates from Kermes or Holly oak (Quercus coccifera L.), an evergreen shrub or small tree which is widely present in the Mediterranean area, were investigated in a greenhouse using a dynamic enclosure technique, Monoterpenes emitted with the highest rates from Quercus coccifera were alpha-pinene, sabinene and beta-pinene. alpha-pinene contributed 41 % to the total monoterpene emission, sabinene 28 % and beta-pinene 25 %. The isoprene emission rate was 0.7 % of the total monoterpene emission rate. Standardisation to 30 degrees C revealed a total monoterpene emission rate of 18.7 mu g gLDW(-1) h(-1). The data show that terpenoid emissions from Kermes oak (Quercus coccifera L.) are qualitatively and quantitatively similar to those of Helm oak (Quercus ilex L.). Both species have to be considered as strong monoterpene emitters, Emissions are considerably higher compared to the emission factor of 1.2 mu g C gLDW(-1) h(-1) which was assumed to represent the monoterpene emission rate from Mediterranean ecosystems at standard conditions in a study about a global model of natural VOC emissions.
The following values have no corresponding Zotero field: periodical: PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION pub-location: ASHURST LODGE, SOUTHAMPTON, HANTS, ENGLAND S04 2AA
Keywords: alpha-pinene; beta-pinene; isoterpene; Mediterranean area; Monoterpene; Quercus coccifera L.; sabinene; terpenoid; VOC emissions